Kinship Terminology: Problems in Some English-Tshivená¸“a Bilingual Dictionaries - Mafela, Munzhedzi James (Lexikos, 2007)
Abstract: With the introduction of a new political dispensation in South Africa; bilingual dictionaries have become a necessary part of daily life. The main function of a bilingual dictionary is to provide one or more equivalents in the target language for the entry words in the source language. Not all bilingual dictionaries realize this objective satisfactorily; Tshivená¸“a bilingual dictionaries included. Some bilingual dictionaries in Tshivená¸“a provide one equivalent instead of all equivalents associated with the entry word of the source language; especially if Tshivená¸“a is the target language. Not providing all equivalents renders a bilingual dictionary inadequate; because users do not always find what they look for. By focusing on kinship terms in some English–Tshivená¸“a bilingual dictionaries; this article discusses examples of inadequate treatment. The article further advocates the inclusion of all possible equivalents under such entry words.Keywords: BILINGUAL DICTIONARY; CROSS-RELATIONSHIP; DICTIONARY USER; EQUIVALENT; INDIGENOUS LANGUAGE; KINSHIP TERMINOLOGY; ORTHO-RELATIONSHIP; SOURCE LANGUAGE; LEXICAL UNIT; LEXICOGRAPHER; RELATIVES; TARGET LANGUAGE; TRANSLATIONOpsomming: Verwantskapsterminologie: Probleme in sommige Engels–Tshivená¸“a tweetalige woordeboeke. Met die invoering van 'n nuwe politieke bedeling in Suid-Afrika het tweetalige woordeboeke 'n noodsaaklike deel van die daaglikse lewe geword. Die hooffunksie van 'n tweetalige woordeboek is om een of meer ekwivalente in die doeltaal vir die trefwoorde in die brontaal te verskaf. Nie alle tweetalige woordeboeke verwesenlik hierdie doel bevredigend nie; Tshivená¸“a tweetalige woordeboeke ingesluit. Sommige tweetalige woordeboeke in Tshivená¸“a verskaf een ekwivalent in plaas van al die ekwivalente wat in verband staan met die trefwoord van die brontaal; veral as Tshivená¸“a die doeltaal is. Deur nie alle ekwivalente te verskaf nie maak 'n tweetalige woordeboek ontoereikend omdat gebruikers nie altyd kry wat hulle soek nie. Deur op verwantskapsterme in sommige Engels–Tshivená¸“a tweetalige woordeboeke te fokus; bespreek hierdie artikel voorbeelde van onvoldoende behandeling. Verder bepleit die artikel die insluiting van alle moontlike ekwivalente onder sulke trefwoorde.Sleutelwoorde: BRONTAAL; DOELTAAL; EKWIVALENT; INHEEMSE TAAL; KRUISVERWANTSKAP; LEKSIKALE EENHEID; LEKSIKOGRAAF; ORTOVERWANTSKAP; TWEETALIGE WOORDEBOEK; VERTALING; VERWANTE; VERWANTSKAPSTERMINOLOGIE; WOORDEBOEKGEBRUIKER